Commuting Time and Household Responsibilities: Evidence Using Propensity Score Matching - J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute for the Study of Labor (IZA), 2015)
The growth in women's participation in the labor force has attracted attention to the gender differences in commuting behavior, and to their implications. This study analyses the relationship between individual commuting behavior and household responsibilities, with a focus on gender differences in that relationship. Using the Dutch Time Use Surveys for the years 2000 and 2005, we analyze the relationship between commuting time, and the time devoted to home production and childcare. To deal with reverse causality, we use Propenstity Score Matching techniques to obtain imputed data for individuals. After reverse causality is taken into account, we find that the effect of home production on commuting time for women is more than double the effect for men, while childcare time has an effect on women's commuting time behavior only. Our results explain why prior studies have found that women have shorter commutes than men, shedding light on the Household Responsibility Hypothesis (HRH).
Keywords: D13; J16; J22; 330; commuting; home production; childcare; propensity score matching; Multinational Time Use Study